Femtosecond laser–assisted pediatric cataract surgery: Bochum formula. Issue 4 (April 2015) - Dick, Burkhard H.; Schelenz, Desiree; Schultz, Tim
Abstract : Purpose : To assess capsulotomy enlargement after femtosecond laser treatment in pediatric cataract surgery and to assess the possible relationship to the patient's age. Setting : Ruhr University Eye Hospital, Bochum, Germany. Design : Prospective case series. Methods : Anterior and posterior laser capsulotomies were performed in cases of pediatric cataract. The Pearson correlation coefficient ( r ) was used to evaluate the relationship between the programmed capsulotomy diameter and the achieved capsulotomy diameter. Linear bivalent regression analysis was used to describe the extent to which the capsulotomy enlargement factor was age dependent. Results : Twenty‐two eyes of 18 children were included in the trial. The mean age was 9.2 years ± 6.08 (SD) (range 0.17 to 18.0 years). The enlargement factors of the capsulotomies showed a highly significant negative correlation with patient age ( r = −0.863; P < .001). In particular, younger children had a distinct deviation from the target diameter. Using linear bivalent regression analysis, an age‐depending correction formula was developed. Conclusion : The Bochum formula for pediatric laser capsulotomies helped minimize the age‐dependent deviation from the targeted diameter. Anterior and posterior laser capsulotomies in children were safe to perform. Financial Disclosure : No author has a financial or proprietary interest in any material or method mentioned.